Cardiac myxoma. Speaking of Two Cases - Fernandini, Oscar (1964)
Two fatal cases of cardiac myxoma (left atrium) that, to our knowledge, are the only ones that occurred in Peru communicates. A review of historical data, histogenesis, clinical aspects, diagnostic problems and surgical treatment of cardiac myxoma is made. The accumulated evidence to date would indicate cardiac myxoma as a true tumor. Emphasis is placed on certain clinical features whose presence should alert the clinician to the possibility of trying a cardiac myxoma. The importance of preoperative diagnosis of these tumors to intracavitary and carry out a planned surgical strike (extracorporeal circulation and hypothermia) is underlined. The risks of an operation to overcast noted when the tumor is found during a planned commissurotomy for mitral stenosis alleged.